Adverse events following mass antibiotic prophylaxis during a Group A Streptococcus outbreak in the Canadian Forces Leadership and Recruit School - Lu, Diane; Strauss, Barbara; Simkus, Kristen; Tepper, Martin; Gagnon, François; Johnson, Noémie; Girard, Eric; Barnes, Kirsten (Canada communicable disease report, 2020)
Background: Between December 2016 and March 2018, two outbreaks of Group A Streptococcus (GAS) infection occurred at the Canadian Forces Leadership and Recruit School. A voluntary mass antibiotic prophylaxis (MAP) program was implemented in March 2018, to interrupt an ongoing GAS outbreak, and to prevent future outbreaks. Methods: Instructors and recruits were offered a one-time intramuscular injection of 1.2 million units penicillin G benzathine (PGB). Individuals with a penicillin allergy were offered azithromycin; 500 mg orally once weekly for four consecutive weeks. Instructors and recruits were also asked to complete a voluntary and anonymous survey one week after receipt of MAP, to detect MAP-related adverse events. Results: MAP was offered to 2,749 individuals; 2,707 of whom agreed to receive it (98.5% uptake). The majority of personnel experienced adverse events in the days following MAP; 92.3% of personnel who received PGB reported localized pain at the injection site, and 70.2% of personnel who received azithromycin reported gastrointestinal symptoms. However, only five cases of serious adverse events were reported, and less than 1% of recruits could not complete their basic military training course because of MAP-related adverse events. Conclusion: The MAP program implemented in March 2018 was the first of its kind in the Canadian Armed Forces, and the largest single use of PGB in a defined group in Canada. It resulted in very few serious adverse events and with minimal impact on military recruits’ successful completion of recruit training.